(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Triassic Los Menucos Group, which fills the homonymous basin, crops out in the Río Negro province (North Patagonian Massif) of Argentina. This unit includes the lower Vera Formation and upper Sierra Colorada Formation (Fig. 1). The lower one is composed of an ignimbritic succession with intercalations of clastic sediments with tabular geometry deposited in continental environments, the thickness of Vera Formation is up to 130 m. The overlying Sierra Colorada Formation is also composed of an ignimbritic succession, up to 20 m in thickness. The current investigation includes the recognition of facies, sedimentary process and provenance analysis. It is based on the observations by Labudía et al. (1995) and Labudía and Bjerg (2001) on the influence of the volcanic environment in the sedimentation of the Vera Formation in the Puesto Tscherig area (Figs. 1, 2). The objective of this contribution is to present a sedimentary facies analysis that allows the interpretation of depositional paleoenvironments. In addition, the aim of this contribution is to quantify the importance that explosive volcanism had on the development of the sedimentary facies. In this manuscript, the White and Houghton (2006) classification scheme for volcaniclastic deposits and their derivatives generated by weathering and erosion, is followed. This scheme is based on the primary depositional mechanisms. Volcaniclastic deposits are accumulations of particles formed by volcanism and mobilized directly by effusive or explosive processes before deposition. Volcaniclastic particles include pyroclastic, autoclastic, hyaloclastic and peperitic fragments. Moreover, White and Houghton (2006) proposed that the term volcaniclastic should not be used for those rocks derived by accumulation of particles originated from weathering and erosion of volcanic rocks, contrary to the suggestions of Fisher (1961). The White and Houghton (2006) classification scheme proposes a sedimentary rock name for those rocks derived by weathering and erosion of volcanic rocks. A suffix can be added indicating type, sorting, or clast morphology; e.g. Smpr denotes a massive sandstone, pumice-rich. The methodology applied includes the measurement of a sedimentary log using standard techniques, facies analysis, and determination of architectural elements (following Herrera and López, 2003; Miall, 2006; Borrero Peña et al., 2008), as well as provenance analysis using ternary diagrams (Dickinson, 1978). Depositional events are stablished considering erosional surfaces. Facies and architectural elements are summarized in Table 1 and stratigraphic relations are shown in figure 2, whereas Table 2 and figure 4 show relative abundances of rock components that are used for provenance analysis using the classic ternary diagrams (Dickinson, 1978). Five facies were recognized. Facies Fl comprises mudstone and fine-grained sandstone with horizontal lamination (Fig. 3d-f) and tabular geometry. Some layers preserve tetrapod footprints and desiccation cracks. Under the microscope tuffaceous matrix, subangular to subrounded clasts, a grain-supported fabric, moderate to good sorting, and mature texture were recognized. This facies gradually overlies the Sh or Sm facies and is truncated by coarser facies. This facies was deposited by settling processes (Miall, 2006). Facies Sh is composed of medium-grained sandstone with horizontal stratification and occasional parting lineation (Fig. 3b, d, f, g). This facies grades vertically from Sm and passes to Fl at the top. Under the microscope tuffaceous matrix, subangular to subrounded clasts, a grain-supported fabric and moderate to good sorting were recognized, and the textural maturity is submature. This facies was deposited in upper-stage plane bed conditions (Miall, 2006). Suprastratal asymmetric deformation structures were observed both in Fl and Sh facies. These structures are interpreted as ballistic projections of lapilli fragments (Manga et al., 2012). The mean orientation of these structures indicates that the lapilli fragments came from the NE. Facies Sm represents medium-to coarse-grained, massive sandstone (Fig. 3b) with tabular geometry. This facies grades from Sgp facies and in turn pass vertically to the Sh facies. Microscopically, isolated pumiceous clasts, tuffaceous matrix, angular to subrounded clasts, matrix-to grain-supported matrix, and poor to moderate sorting were noted, defining a submature textural maturity. Analogue deposits were interpreted as originated by dilute flows (which at syneruptive stage are Type 2) or hyperconcentrated flows (Smith and Lowe, 1991). Pierson and Scott (1999) and Lirier et al. (2001) interpreted similar deposits as basal diluted layers at the bottom of debris flows or as hyperconcentrated flows. Jo (2003) considered a rapid sedimentation from debris flows. The absence of chute and pool structures may indicate that deposition processes could be related to hyperconcentrated flows or intermediate stages between Type 2 and diluted flows. Facies Sr comprises fine-grained sandstone with ripple cross-lamination (Fig. 3e) in thin beds, typically interbedded with Fl facies. Under the microscope tuffaceous matrix, subrounded to subangular clasts, a grain-supported fabric and good sorting were observed, providing a mature texture. This facies was deposited by migration and aggradation of current ripples generated by dilute flows under low flow regime (Miall, 2006). Paleocurrent measurements indicate that ripple migration was preferentially towards SW (250°). The close spatial relationship with the Fl facies allows to infer that the ripple drift was linked to standing water bodies, possibly associated with stages of surface water recharge. Facies Sgp represents medium-to coarse-grained, massive sandstone composed of glass and pumice fragments (Fig. 3a-c, f). Sgp strata (up to 9 m thick) show lobate shape and exfoliation weathering (onion exfoliation). Pumiceous clasts are abundant and smaller than 15 cm, and intraformational Fl clasts are common with sizes up to 30 cm. Under the microscope tuffaceous matrix, highly angular to subrounded clasts, a matrix-supported fabric and moderate to poor sorting are noted, textural maturity is immature. This facies was most likely deposited by debris flows (Palmer and Neall, 1991; Smith and Lowe, 1991; Herrera and López, 2003; Miall, 2006; Borrero Peña et al., 2008). The low content of non-volcanic clasts and the common conservation of primary volcanic features in the pumice fragments suggest that these deposits originated by reworking of a non-welded volcaniclastic deposit (Smith and Lowe, 1991; McPhie et al., 1993). Two architectural elements were defined based on facies spatial relationships: Volcaniclastic Sedimentation (VS sensu Borrero Peña et al., 2008) and Floodplain Fines (FF sensu Miall, 2006), which occur interbedded. SV is mainly composed of Sgp and Sm facies, with subordinate contribution of Sh facies. It is characterized by an erosional basal boundary and a gradual upper contact (to FF element). This architectural element represents multi-episodic sedimentation from debris flows and/ or hyperconcentrated flows to diluted currents and originated from re-sedimentation of a non-welded volcaniclastic deposit. FF element is composed of Sr and Fl facies. This element records alternating deposition from settling and traction in standing water bodies. In fact, the Sr facies could represents surface water recharge. Five depositional episodes are defined considering erosional surfaces (Fig. 2); each depositional episode suggests that settling/ traction processes evolved from debris flows and/ or hyperconcentrated flows to stream flows by dilution, either by sedimentation or water addition. The resulting vertical stacking pattern of each depositional episode is a fining-upward succession including, from base to top, the following facies: Sgp, Sm, Sh, Sr and Fl facies (Fig. 5). This spatial distribution of facies is comparable with the model of composite sediment flow deposits (Sohn et al., 1999; Lirier et al., 2001). According to this model, the resulting successions are characterized by debris flow deposits in the near-vent position, which are replaced by hyperconcentrated flow and streamflow deposits toward the downstream zone (Fig. 5). On the other hand, the absence of channelized deposits linked to more complex tractive flows could be related to individual depositional episodes during short time intervals (Smith, 1991a). Besides, the presence of desiccation cracks and/or fossil content infer a considerable time of subaerial exposure (Smith, 1991a). Facies and facies association, petrography and allocation of depositional episodes allow to propose that these lahar-runout deposits could correspond to a syn-eruptive stage (Smith, 1986; Smith 1991a,b; Smith and Lowe, 1991; McPhie et al., 1993; Bahk and Chough, 1996). These authors suggest that the syn-eruptive stage is dominated by debris from hyperconcentrated flows, monolithological volcanic compositions, deposits dominated by sandstone, and high aggradation rates. However, Lirier et al. (2001) argued that debris and hyperconcentrated flows are not directly linked with a syn-eruptive stage, because they could be triggered by several mechanisms, even during inter-eruptive stages. It should be noted in this regard that the record of ballistic projections supports a syn-eruptive stage. Finally, the recognized stacking pattern, the paleocurrent directions measured in the Sr and Sh facies, and the direction of ballistic projections all favor the presence of a volcanic edifice located to the northeast of the study area. This interpretation is consistent with a volcanic caldera located to the south of Cerro La Laja (Ducart, 2007).